Targeting pancreatic stellate cells in chronic pancreatitis: Focus on therapeutic drugs and natural compounds - Wu, Yang; Zhang, Chun; Guo, Mei; Hu, Weikang; Qiu, Yangling; Li, Mengran; Xu, Dong; Wu, Pengfei; Sun, Jing; Shi, Run; Zhang, Zili; Jiang, Kuirong (Frontiers in Pharmacology, 2022)
Chronic pancreatitis (CP) is a precancerous illness linked to pancreatic ductal adenocarcinoma (PDAC), although the evolutionary mechanism is uncertain. CP is distinguished by severe fibrosis caused by the activation of pancreatic stellate cells (PSCs). The current clinical therapeutic protocol for CP lacks specific therapeutic medicines for the prevention and suppression of inflammation and fibrosis aggravating in CP. More research on specifically targeting PSCs would help facilitate the development of novel therapies for pancreatic fibrosis. Notably, using natural compounds from medicinal plants as new antifibrotic agents has become a focus of recent research and is widely employed as an alternative and complementary approach. Our goal was to shed light on the role of PSCs in the development of CP and provide a focused update on the new potential therapeutic strategies against PSCs in CP models. Future studies can refer to these possible strategies for drug design, bioavailability, pharmacokinetics, and other issues to obtain better clinical outcomes for treating CP.